INANG-INANG DI PASAR ANGSO DUO JAMBI 1974 – 2005 - Nova Riyanti, Nur Agustiningsih (Universitas Batanghari Jambi, 2017)
AbstracThis study aims to describe Inang-inang economy activities at Angso Duo Market of Jambi from the emergence to the effects of economic life of the perpetrators, especially from the acquisition of income earned. The research method used is historical method, covering the stages of Heuristik, Source Critique, Interpretation, and Historiography. The approach used is a theoretical approach that is multidisciplinary by applying other social sciences concepts such as economics and sociology. The results showed that the economic activities act of Inang-inang as traders at Angso Duo Market of Jambi. Although only a trader, but this profession still remains to be one of the livehood options for those who are involved in working on it. This is because it can be improve the welfare of the Inang-inang go through it.Keywords : Inang-inang, Angso Duo Market, Jambi City